How are female rugby players affected by contact breast injuries and exercise-induced breast pain - an international survey - Bibby, K.; Comyns, T. M.; Cahalan, R.; Kenny, I. C. (Research in Sports Medicine, 2024)
Female Rugby Union players were affected by contact breast injuries (CBI) and exercise-induced breast pain (EIBP). Hundred and eighty-two female Rugby players from 25 different countries reported incurring a CBI or EIBP which affected sport performance. A higher percentage of 7s players (7s: 64.3%, 15s: 51.9%) reported at least one CBI over a 12-month period. EIBP frequency, during the same period, was notably low for 7s and 15s. Sprinting, jumping and running were the most frequent activities precipitating the severest EIBP. Being tackled or tackling most frequently caused a CBI. Respondents affected by either CBI (57.3%) or EIPB (51.3%) reported always playing-on during matches despite their pain or injury. Between 19.4% and 32.1% of the respondents did not have a CBI or EIBP prevention strategy. A paucity of player knowledge on prevention strategies was noted, indicating a need for education addressing breast pain and injury among players.